INCREASING MULTICULTURAL AWARENESS THROUGH EXPERIENTIAL LEARNING MODEL - Eny Usmawati (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2022)
This study aims to increase multicultural awareness in the effectivenessofthe Experiential Learning model  in  multicultural group students (Javanese and Chinese tribes) at SMP 1 Negeri Parung Bogor .  Within group or individual  design and equivalent materials design  were the designs in this study.  Meanwhile, the data  collection instrument in this study uses a multicultural awareness scale, to increase multicultural awareness of experiential learning  model learners as an instrument in  this research.  Uji  nonparametric statistics and  visual data analysis is a data  analysis in  this study to see changes in multicultural awareness.  Increasing multicultural awareness of multicultural group students (Javanese and Chinese tribes) at SMP Negeri 1 Parung Bogor in using model Experiential Learning  effectively.